APLIKASI PUPUK NITROGEN DAN CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN ABU BOILER TERHADAP SERAPAN HARA NPK OLEH TANAMAN PADI (Oryza sativa L.) - Siregar, Martin Donal Wido; Yetti, Husna; ', Nelvia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rice production decreasingly in Riau can be caused by the loses of soil nutrient consequence due to soil leached, plant reserving and using of the same macro fertilizer continuously, that resulting unavailable nutrient for rice plant. The research aimed to get interaction among N fertilizer and mixture of Palm oil empty fruit bunch (POEFB) compost with boiler ash on growth and uptake N, P dan K by rice. The research has conducted in Rambai island village, Kampar Country, Riau province from December 2012 to March 2013. The method of research is experimentally with using a factorial completely randomized design with two factors. The first factor is N fertilizer with 2 level ( N1 = 100 kg N/ha and N2 = 200 kg N/ha). The second factor is POEFB compost mixed with boiler ash with 4 levels (A0 = without compost of POEFB and boiler ash, A1 = 5 tons/ha compost of POEFB + 500 kg boiler ash/ha, A2 = 5 tons/ha compost of POEFB + 750 kg boiler ash/ha and A3 = 5 tons/ha compost of POFEB + 1000 kg boiler ash/ha). The research of parameter are plant height, maximum number of tillers, dry weight to shoot and N, P, K nutrient uptake. The result showed that the application of 5 ton/ha compost of POEFB + 750 kg boiler ash/ha is tend to increase effect on plant height, maximum number of tillers, dry weight to shoot by rice compart 5 ton compost POEFB + 500 kg boiler ash/ha and control well the follow 100-200 kg N/ha. Nutrient uptake N, P and K by  rice plants is tend to increase with increasing dosis 750 kg boiler ash/ha as mixing 5 ton/ha compost POEFB be compared mixed with 5 ton/ha compost POFEB and 500 kg boiler ash/ha or control well the follow 100-200 kg N/ha.     Keyword : Compost, boiler ash, nitrogen fertilizer and rice.